The potential impact of azithromycin in idiopathic pulmonary fibrosis. Issue 2 (14th February 2019) - Macaluso, Claudio; Maritano Furcada, Joaquín; Alzaher, Omamah; Chaube, Ritesh; Chua, Felix; Wells, Athol U.; Maher, Toby M.; George, Peter M.; Renzoni, Elizabeth A.; Molyneaux, Philip L.
There is growing evidence of the role of infection in the pathogenesis and progression of idiopathic pulmonary fibrosis (IPF) [1–4]. Over a third of patients with IPF will be hospitalised, at least once, during the course of their disease [5]. These events not only carry a significant morbidity and mortality, but also a healthcare cost and burden [6]. Indeed, there is a growing recognition of these events as a potential marker for disease progression, reflected in the growing consensus to include such events as outcomes in future clinical trials [7]. Therefore, treatments that reduce the risk of hospitalisation could have a major impact. While recent evidence suggests that macrolide antibiotics may improve survival in acute exacerbations of IPF [8], to date there has been no study examining the potential role of prophylactic macrolides on reducing these emergency admissions or disease progression. This retrospective, observational study aimed to evaluate the impact of long-term azithromycin treatment in reducing hospitalisation rates in IPF patients. Prophylactic azithromycin is a safe and well tolerated therapy in patients with IPF and may reduce hospital admissions. Prospective mechanistic studies are urgently needed. http://ow.ly/oBOn30mDaaL